INCIDENCE OF BREECH PRESENTATION AND ITS ASSOCIATION WITH FETAL/MYOMETRIAL LESIONS IN KANO - Rabiu A; Abubakar SA (Ntec Specialist, 2017)
Background: The entrance of the fetal buttocks or lower extremities into the maternal pelvic inlet is defined as breech presentation. It complicates 3-4% of all pregnancies. The occurrence of breech presentation decreases with advancing gestational age. Both myometrial and fetal lesions have been linked with persistence of breech presentation. Methodology: It was a prospective study conducted at Aminu Kano Teaching Hospital. Ethical approval was obtained from the hospital ethics committee. Information on socio-demographic characteristics was sought and obtained on a questionnaire after obtaining informed consent. Obstetric sonograms were obtained using 3.5 MHz linear transducer connected to Mindray Digital Ultrasound Imaging System (Model DC6; Shenzhen Mindray Biomed Electronics, Shenzhen, China). Obstetric correlates that were determined and recorded on the questionnaire were the lie, presentation, estimated gestational age, myometrial and fetal lesions. The data were analyzed using SPSS Electronic Software Version 19 (SPSS Inc, IL, Chicago, USA). Chi-squared test was used for categorical data and P Value of less than 0.05 was considered statistically significant. Results: A total of 300 pregnant women were recruited for the study. The mean age± SD was 27.3±5.20. The incidence of breech presentation was highest below the gestational age of 28 weeks (14.3%); the least (1.6%) was above the gestational age of 36 weeks. There was no statistically significant association between breech presentation and myometrial or fetal lesion (P=0.213; P=0.787 respectively). Conclusion: There was low incidence of breech presentation at term (1.6%). The incidence of breech presentation has an inverse relation with an increasing gestational age. Myometrial and fetal lesions were not statistically associated with occurrence of breech presentation.